1997
DOI: 10.1007/s004410050867
|View full text |Cite
|
Sign up to set email alerts
|

GDNF improves survival and reduces apoptosis in human embryonic dopaminergic neurons in vitro

Abstract: Dopamine cell death is the primary problem limiting the value of neurotransplantation in human patients with Parkinson's disease. To address this problem, we added glial cell line-derived neurotrophic factor (GDNF) to cultures of embryonic dopaminergic neurons obtained from human and from Bonnet monkey (Macaca radiata) in an effort to reduce apoptotic cell death and improve overall cell survival. Tissue from three human embryos, 7-8 weeks post-conception, and one 9-week post-conception monkey embryo were disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(49 citation statements)
references
References 14 publications
2
46
0
1
Order By: Relevance
“…Nevertheless, the data would suggest that Lenti-GDNFinfected neural precursors, following differentiation, secrete amounts of biologically active GDNF sufficient to elicit neurotrophic effects on DA neurons in culture. These effects are consistent with previous in vitro studies using purified recombinant GDNF (Lin et al, 1993;Clarkson et al, 1997;Burke et al, 1998).…”
Section: Lenti-gdnf-infected Ns Increase the Survival Of Cotransplantsupporting
confidence: 92%
“…Nevertheless, the data would suggest that Lenti-GDNFinfected neural precursors, following differentiation, secrete amounts of biologically active GDNF sufficient to elicit neurotrophic effects on DA neurons in culture. These effects are consistent with previous in vitro studies using purified recombinant GDNF (Lin et al, 1993;Clarkson et al, 1997;Burke et al, 1998).…”
Section: Lenti-gdnf-infected Ns Increase the Survival Of Cotransplantsupporting
confidence: 92%
“…Given the methodological and biological difficulties in studying neuronal cell death in human brains, in vitro models of dopaminergic cell death are powerful, as they allow the study of neurodegeneration as well as novel therapeutic strategies. Nevertheless, with very few exceptions (Clarkson et al, 1997), it has not been possible to examine directly the toxic effects of neurotoxins and protective effects of multiple factors for normal human dopaminergic neurons, because the availability of human dopaminergic neurons derived from fetal material is extremely limited. In the present study, we showed that hESCs can provide an unlimited source of normal human dopaminergic neurons for in vitro studies of neurotoxic and neuroprotective processes that might be related to PD.…”
Section: Discussionmentioning
confidence: 99%
“…GDNF treatment has also been reported to reduce apoptosis in dopaminergic neurones cultured from embryonic rat [14,15] and human [16] midbrain. GDNF can also protect cultured dopaminergic neurones from lipopolysaccharide-induced degeneration, a model of neuroinflammation [17].…”
Section: Effects Of Gdnf In Vitromentioning
confidence: 99%
“…Increases Tyrosine Hydroxylase expression [8] Promotes survival of mesencephalic cultures [6,9] Promotes morphological differentiation [10] Protects from MPP+ neurotoxicity [12,13] Protects from 6-OHDA neurotoxicity [11] Decreases apoptosis [14,15,16] Protects from LPS neurotoxicity [17] …”
Section: Conflict Of Interestmentioning
confidence: 99%